2016
DOI: 10.1159/000446808
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Apigenin on Losartan Metabolism and CYP2C9 Activity in vitro

Abstract: Background: CYP2C9 is one of the most important phase I drug-metabolizing enzymes in liver. The objective of this work was to investigate the effects of apigenin on the metabolism of losartan and human CYP2C9 and rat CYP2C11 activity in vitro. Methods: Different concentrations of apigenin were added to a 100 mmol/l Tris-HCl reaction mixture containing 2 pmol/ml recombinant human CYP2C9.1, 0.25 mg/ml human liver microsomes or 0.5 mg/ml rat liver microsomes to determine the half maximal inhibition or a half-maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…CYP2C19 wild type is the fastest metabolism type in all of CYP2C19 genotype. [ 25 ] The ultrafast drug metabolism forces to increase dosages, which result in kidney toxicity and nephropathy. Hence, the use of the prodrug and tailored drug to protect against nephropathy is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…CYP2C19 wild type is the fastest metabolism type in all of CYP2C19 genotype. [ 25 ] The ultrafast drug metabolism forces to increase dosages, which result in kidney toxicity and nephropathy. Hence, the use of the prodrug and tailored drug to protect against nephropathy is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…After 4 weeks of feeding with a diet containing 3% green tea polyphenols, the expression and metabolic activity of hepatic CYP3A in mice decreased, resulting in an elevated plasma level of a CYP3A substrate drug, triazolam (Ikarashi et al., 2016). Apigenin has been shown to exhibit a competitive inhibitory effect on human CYP2C9 in liver microsomes and to reduce losartan metabolism in vitro (Wang et al., 2016). In vitro studies have shown that soy isoflavones, such as genistein and daidzein, were able to inhibit the activities of most human liver microsomal cytochromes P450 (except CYP2A6 and CYP2B6) by a noncompetitive mechanism (Kopecna‐Zapletalova et al., 2017).…”
Section: Current Strategies For Improving Bioavailability Of Nutraceu...mentioning
confidence: 99%